Groundwater quality of the coastal aquifers in the eastern part of Thermaikos Gulf (from Aggelochori to Kallikrateia) - Pavlou, A.; Soulios, G.; Dimopoulos, D.; Tsokas, G.; Mattas, C.; Kazakis, N.; Voudouris, K. (Bulletin of the Geological Society of Greece, 2013)
The study area is located in the coastal area of the eastern Thermaikos Gulf, covering an area of 252 km2. The area is characterised by intense agricultural activity, and during the past few years it has undergone considerable residential development. From a geological point of view, the area consists of Quaternary alluvial coastal deposits, river terraces and Neogene deposits (marly limestones and sandstone- marl series). The bedrock formations are Jurassic limestone and Mesozoic granite. The main aquifer system is developed within the sand, gravel, and sandstone layers of the Quaternary deposits as well as within the sandstone-marl series. This paper investigates the relationship between the groundwater quality and groundwater level. Groundwater sampling and water level measurements took place in April and September 2010. The results of chemical analyses indicate degradation of the groundwater quality. The sources of the groundwater pollution are seawater intrusion due to the overexploitation of the coastal aquifers, fertilizers from the agricultural activities and the disposal of untreated wastewater in torrents.